A PRECONDITIONING FRAMEWORK FOR SEQUENCES OF DIAGONALLY MODIFIED LINEAR SYSTEMS ARISING IN OPTIMIZATION - BELLAVIA, STEFANIA; DE SIMONE, VALENTINA; DI SERAFINO, DANIELA; MORINI, BENEDETTA (SIAM journal on numerical analysis, 2012)
We propose a framework for building preconditioned for sequences of linear systems of the form (A + ∆ k )x k = b k , where A is symmetric positive semidefinite and ∆ k is diagonal positive semidefinite. Such sequences arise in several optimization methods, e.g., in affine-scaling methods for bound-constrained convex quadratic programming and bound-constrained linear least squares, as well as in trust-region and overestimation methods for convex unconstrained optimization problems and nonlinear least squares. For all the matrices of a sequence, the preconditioners are obtained by updating any preconditioner for A available in the LDL T form. The preconditioners in the framework satisfy the natural requirement of being effective on slowly varying sequences; furthermore, under an additional property they are also able to cluster eigenvalues of the preconditioned matrix when some entries of ∆ k are sufficiently large. We present two low-cost preconditioners sharing the above-mentioned properties and evaluate them on sequences of linear systems generated by the reflective Newton method applied to bound-constrained convex quadratic programming problems and on sequences arising in solving nonlinear least-squares problems with the regularized Euclidean residual method. The results of the numerical experiments show the effectiveness of these preconditioners.